Ethics of Using Social Media for Learning: Encouraging Appreciation and Responsibility - Erwin Erwin; Andi Muhammad Dakhalan (Yayasan Adra Karima Hubbi, 2024)
In today’s era that is all about technology, social media is an important need for many people. Social media is now inherent in social circles, especially the current millennial generation. Almost all teenagers, adults and even children have social media. It is not uncommon for us to always be connected to the outside world through social media. The use of the internet through social media has presented a web forum that can form an online community. The purpose of the study is to find out the learning attitudes that can encourage students to use social media in learning in high school, as well as have a potential impact in encouraged, respectful and responsible attitudes in the use of social media as learning. The research uses a quantitative method that can be used to determine the results of research on student learning activities. The data was obtained from documents in the form of books and journals related to the theme, finally this research focused on encouraging students to social media as a form of attitude and responsibility in the world of Education. The results of these observations explain the ethics of using social media for learning in encouraging students to act respectfully and responsibly which can play an important role in encouraging the use of social media for students to be more concerned about their responsibilities. In this use, it is inseparable from an ability and a deficiency in the attitude of students if applied in learning, therefore educators and parents are very influential. The conclusion obtained from the study is that in encouraging the ethics of using social media today, social media has shown great hope in encouraging education. In this observation, the use of social media can be used as an attitude of respect and responsibility. With the use of social media, you can form good ethics to encourage mutual respect.